A reference image‐based method for optimization of clinical immunohistochemistry. Issue 2 (19th February 2015) - Kap, Marcel; Lam, King H; Ewing‐Graham, Patricia; Riegman, Peter
<x xml:space="preserve">Abstract</x> Aims Cold ischaemic and formalin fixation time (CIT and FFT) are considered to be crucial parameters for intralaboratory variation in immunohistochemistry (IHC). Here we describe a new method to optimize IHC, by using control tissue blocks with known pre‐analytical history and comparing the IHC outcome with digitized reference slides. Methods and results Tissue specimens (two per tissue type) were divided into eight samples, which were subjected to different CIT and FFT. Immunohistochemistry was performed with 34 routinely used antibodies, following standard operating procedures. Relative staining intensity of four sections per slide was scored. Of the antibodies studied, seven were influenced by CIT, 13 by FFT and five by both parameters. IHC protocols were adapted until most sections on the slide showed the same intensity. Changing the antibody dilution for 10 protocols and the antigen retrieval method for six protocols improved the consistency of the IHC staining. Nine protocols could not be optimized. The optimized staining results were compared to reference slides and were found to be of adequate quality. Conclusions It was possible to optimize most IHC protocols by adapting the analytical, rather than the pre‐analytical, phase. If global references can be established, this method could decrease interlaboratory variation, preceding standardization of the pre‐analytical workflow.